The Potential Sources of Transmission and Distribution of Lymphatic Filariasis in Semarang City, Central Java, Indonesia - Nurjazuli, Nurjazuli; Santjaka, Aris (Unnes Journal of Public Health)
Lymphatic Filariasis (LF) is a neglected tropical disease caused by filarial worms. Semarang City has an increasing number of LF. The aim of this study was to investigate potential sources of transmission and distribution of LF. It was descriptive research using cross-sectional design. The sample were 28 LF cases. The variables studied were level of knowledge, physical and biological environmental factors, and provision of health service. Data were collected using interviews and observation. Data were analyzed descriptively and spatially. The results showed that LF cases were distributed in center of Semarang City, especially in the coastal area.  Poor drainage and stagnant water around the houses were potential breeding places for mosquitos, which are suspected as a vector of LF transmission. Poor knowledge of LF, physical and biological environmental factors around the houses of LF patient houses may possibly be sources of distribution and transmission of LF.